2013
DOI: 10.1111/jonm.12134
|View full text |Cite
|
Sign up to set email alerts
|

Safeguarding in medication administration: understanding pre-registration nursing students' survey response to patient safety and peer reporting issues

Abstract: Nurse managers are role models for nursing students in the clinical setting. Nursing management must lead, by example, the patient safety agenda in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Focus group discussions with final year students in a study completed by Adhikari et al (2014) revealed limited knowledge, insufficient understanding, lack of confidence and a need for more learning sessions on medication management and applied pharmacology. A lack of knowledge in pharmacology may be attributed to a lack of in-service training and integration of theory and practical (Lim and Honey, 2006;Ndosi and Newell, 2009;Davis, 2010) and has implications for patient safety (Andrew and Mansour, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focus group discussions with final year students in a study completed by Adhikari et al (2014) revealed limited knowledge, insufficient understanding, lack of confidence and a need for more learning sessions on medication management and applied pharmacology. A lack of knowledge in pharmacology may be attributed to a lack of in-service training and integration of theory and practical (Lim and Honey, 2006;Ndosi and Newell, 2009;Davis, 2010) and has implications for patient safety (Andrew and Mansour, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To ensure patient safety (Andrew and Mansour, 2014) nurses need a good foundational knowledge of bioscience. Consequently, the South African Nursing Council (SANC) has legislated for the inclusion of biological and natural sciences (anatomy, physiology, chemistry, biophysics, microbiology and parasitology) *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Although nurse researchers did not provide information related to what students were thinking while administering medications, some did report that students and new graduates expressed concern about patient safety [6,9,11,13,15] . Student comments during Thompson and Bonnel's [11] pharmacologic simulation debriefing and evaluation indicated, "they had learned a valuable lesson [about medication administration] in a safe environment."…”
Section: Relevant Scholarshipmentioning
confidence: 99%
“…Student comments during Thompson and Bonnel's [11] pharmacologic simulation debriefing and evaluation indicated, "they had learned a valuable lesson [about medication administration] in a safe environment." In a qualitative questionnaire following a medication administration scenario, Andrew and Mansour [15] also reported student concerns related to their experiences with patient safety. Third year nursing student responses encompassed four themes: a) protecting patient safety (actions they would take to protect patients from errors), b) willingness to compromise (or act outside the boundaries of correct medication procedures or policies), c) avoiding responsibility (not wanting to get involved in medication errors or accepting that potential errors may happen to them), and d) consequences resulting from actions (concern that there may be penalties or backlash if they report unsafe practices).…”
Section: Relevant Scholarshipmentioning
confidence: 99%
See 1 more Smart Citation